Pulmonary Arteriovenous Malformations and Cerebral Abscess Recurrence in a Child With Hereditary Hemorrhagic Telangiectasia. Issue 3 (April 2015) - Giordano, Paola; Sangerardi, Maria; Suppressa, Patrizia; Lastella, Patrizia; Attolini, Ettore; Valente, Federica; Fiorella, Maria L.; Lenato, Gennaro M.; Sabbà, Carlo
<x xml:space="preserve">Abstract</x> Background: A 17-year-old boy was referred to our center with a history of brain abscess (BA) recurring after 9 years. The patient reported 2 previous treatments for pulmonary arteriovenous malformations, sporadic nosebleeds, and familial history for epistaxis. Clinical investigations revealed arteriovenous malformations in lung, brain, and liver, as well as mucocutaneous telangiectases. A definite diagnosis of hereditary hemorrhagic telangiectasia was made based on clinical criteria and confirmed by genetic analysis. This is the first report of BA recurrence at the end of pediatric age. Conclusions: The present case and the literature review of all cases of BA thus far reported highlight the need to raise the suspicion of a pulmonary arteriovenous malformations, both isolated and in the context of a possible hereditary hemorrhagic telangiectasia, for any case of BA of unexplained etiology, in children as well as in adults.